PD-L1 and Immune Infiltration of m6A RNA Methylation Regulators and Its miRNA Regulators in Hepatocellular Carcinoma. (17th May 2021) - Lin, Yingxue; Yao, Yinhui; Wang, Ying; Wang, Lingdi; Cui, Haipeng
Abstract : Background . The aim of this study was to systematically evaluate the relationship between the expression of m 6 A RNA methylation regulators and prognosis in HCC. Methods . We compared the expression of m 6 A methylation modulators and PD-L1 between HCC and normal in TCGA database. HCC samples were divided into two subtypes by consensus clustering of data from m 6 A RNA methylation regulators. The differences in PD-L1, immune infiltration, and prognosis between the two subtypes were further compared. The LASSO regression was used to build a risk score for m 6 A modulators. In addition, we identified miRNAs that regulate m 6 A regulators. Results . We found that fourteen m 6 A regulatory genes were significantly differentially expressed between HCC and normal. HCC samples were divided into two clusters. Of these, there are higher PD-L1 expression and poorer overall survival (OS) in cluster 1. There was a significant difference in immune cell infiltration between cluster 1 and cluster 2. Through the LASSO model, we obtained 12 m 6 A methylation regulators to construct a prognostic risk score. Compared with patients with a high-risk score, patients with a low-risk score had upregulated PD-L1 expression and worse prognosis. There was a significant correlation between risk score and tumor-infiltrating immune cells. Finally, we found that miR-142 may be the important regulator for m 6 A RNA methylation in HCC. Conclusion . Our results suggest that m 6 A RNA methylation modulators may affect the prognosis through PD-L1 and immune cell infiltration in HCC patients. In addition, the two clusters may be beneficial for prognostic stratification and improving immunotherapeutic efficacy.